Multiplicity dependence of ϒ production at forward rapidity in pp collisions at s=13 TeV - Acharya, S.; Adamovã, D.; Adler, A.; Aglieri Rinella, G.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S.U.; Ahuja, I.; Akindinov, A.; Al-Turany, M.; et al. (Elsevier, 2025)
The measurement of Υ(1S), Υ(2S), and Υ(3S) yields as a function of the charged-particle multiplicity density, d𝑁ch∕d𝜂, using the ALICE experiment at the LHC, is reported in pp collisions at √𝑠 = 13 TeV. The Υ meson yields are measured at forward rapidity (2.5 < 𝑦 < 4) in the dimuon decay channel, whereas the charged-particle multiplicity is dfined at central rapidity (|𝜂| < 1). Both quantities are divided by their average value in minimum bias events to compute the self-normalized quantities. The increase of the self-normalized Υ(1S), Υ(2S), and Υ(3S) yields is found to be compatible with a linear scaling with the self-normalized d𝑁ch∕d𝜂, within the uncertainties. The self-normalized yield ratios of excited-to-ground Υ states are compatible with unity within uncertainties. Similarly, the measured double ratio of the self-normalized Υ(1S) to the self-normalized J/𝜓 yields, both measured at forward rapidity, is compatible with unity for self-normalized charged-particle multiplicities beyond one. The measurements are compared with theoretical predictions incorporating initial or final state effects.
Keywords: LR-115 nuclear track detectors; Radon measurement; https://purl.org/pe-repo/ocde/ford#1.03.04